The Unequal Effect of Income on Risk of Overweight / Obesity of Whites and Blacks with Knee Osteoarthritis; The Osteoarthritis Initiative - Assari, Shervin (J Racial Ethn Health Disparities, 2020)
BACKGROUND: Although the protective effect of socioeconomic status (SES) against risk of overweight/obesity is well established, such effects may not be equal across diverse racial and ethnic groups, as suggested by the Marginalization-related Diminished Returns (MDR) theory. AIMS: Built on the MDR theory, this study explored racial variation in the protective effect of income against overweight/obesity of Whites and Blacks with knee osteoarthritis (OA). METHODS: This cross-sectional study used baseline data of the OA Initiative, a national study of knee OA in the United States. This analysis included 4,664 adults with knee OA, which was composed of 3,790 White and 874 Black individuals. Annual income was the independent variable. Overweight/obesity status (body mass index more than 25 kg/m2) was the dependent variable. Race was the moderator. Logistic regressions were used for data analysis. RESULTS: Overall, higher income was associated with lower odds of being overweight/obesity. Race and income showed a statistically significant interaction on overweight/obesity status, indicating smaller protective effect of income for Blacks compared to Whites with knee OA. Race-stratified regression models revealed an inverse association between income and overweight/obesity for White but not Black patients. CONCLUSIONS: While higher income protects Whites with knee OA against overweight/obesity, this effect is absent for Blacks with knee OA. Clinicians should not assume that the needs of high-income Whites and Blacks with knee OA are similar, as high-income Blacks may have greater unmet needs than high income Whites. Racially tailored programs may help reduce the health disparities between Whites and Blacks with knee OA. The results are important given that elimination of racial disparities in obesity is a step toward eliminating racial gap in the burden of knee OA. This is particularly important given that overweight/obesity is not only a prognostic factor for OA but also a risk factor for cardiometabolic diseases and premature mortality.